Analyzing Flooding Dynamics and Resilience of a Social-Ecological System (International Journal of Built Environment and Sustainability, 2025)
Amid escalating climate change and other factors, communities in vulnerable areas like Tagum City, Davao del Norte, Philippines, face increasing risks of severe flooding, threatening their safety, livelihoods, and well-being. This highlights the urgent need for comprehensive analysis of flood dynamics and community resilience within a social-ecological system framework, addressing the critical gap in local-level research to inform effective flood risk management strategies. This study employed a combined systematic literature review, Fuzzy Delphi Method, and Analytical Hierarchy Process to develop a Flood Resilience Index (FRI) and resilience map using QGIS. The findings underscore that a significant portion of Tagum City exhibits medium resilience to flooding, with an FRI of 3.221. Notably, several towns identified as medium resilient, including Bincungan (2.801), Pandapan (2.661), Busaon (2.910), and Liboganon (2.660), face heightened vulnerability due to the potential for high flood water levels, exceeding critical thresholds, with a peak level of 11 meters for a projected 5-year return period. The study highlights the interconnectedness of social-ecological components, emphasizing that overall system resilience depends on its weakest elements. To enhance resilience in flood-vulnerable areas, it is crucial to strengthen economic, institutional, and socio-cultural support systems through targeted activities, policies and programs. This research provides crucial insights into the intricate relationship between flooding and resilience, serving as a foundation for informed decision-making and proactive measures to mitigate flood risks, enhance community well-being, and advance climate action for a more resilient and sustainable Tagum City and similar environments.
Keywords: Adaptive capacity, Flood Resilience Index, Analytical Hierarchy Process.